2012
DOI: 10.1371/journal.pone.0034060
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Mediated Inhibition of Dengue Virus Multiplication and Entry in HepG2 Cells

Abstract: Background Dengue virus-host cell interaction initiates when the virus binds to the attachment receptors followed by endocytic internalization of the virus particle. Successful entry into the cell is necessary for infection initiation. Currently, there is no protective vaccine or antiviral treatment for dengue infection. Targeting the viral entry pathway has become an attractive therapeutic strategy to block infection. This study aimed to investigate the effect of silencing the GRP78 and clathrin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 86 publications
3
35
0
Order By: Relevance
“…Regarding hepatic cells, small interfering RNAs (siRNA) silencing experiments revealed that all DENV serotypes enter Huh7 cells through clathrin-mediated endocytosis, and that DENV-2 requires early to late endosome trafficking (Ang et al, 2010). Clathrin-mediated-endocytosis dependence of DENV entry in HepG2 cells was demonstrated by siRNA silencing of target genes as well (Alhoot, Wang and Sekaran 2012). Macropinocytosis was also identified as one of the DENV entry pathways in these cells, although clathrin-mediated endocytosis was the predominant entry route (Suksanpaisan, Susantad and Smith 2009).…”
Section: Entry Pathwaysmentioning
confidence: 99%
“…Regarding hepatic cells, small interfering RNAs (siRNA) silencing experiments revealed that all DENV serotypes enter Huh7 cells through clathrin-mediated endocytosis, and that DENV-2 requires early to late endosome trafficking (Ang et al, 2010). Clathrin-mediated-endocytosis dependence of DENV entry in HepG2 cells was demonstrated by siRNA silencing of target genes as well (Alhoot, Wang and Sekaran 2012). Macropinocytosis was also identified as one of the DENV entry pathways in these cells, although clathrin-mediated endocytosis was the predominant entry route (Suksanpaisan, Susantad and Smith 2009).…”
Section: Entry Pathwaysmentioning
confidence: 99%
“…Among these lectins, dendritic cellspecific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) has been identified as a DENV receptor in immature dendritic HepG2 Laminin receptor 1 [40] GRP78 2 [37][38][39] K562 Glycosphingolipid 1-4 [44] HUVEC Heparan sulfate 4…”
Section: Receptors In Mammalian Cellsmentioning
confidence: 99%
“…It is possible that the entry pathway(s) utilized by the virus may be cell type dependent. Two recent RNA interference studies for dengue virus entry and multiplication into monocytes and HepG2 cells show dependence on clathrin heavy chain (CHC) and dyamin-2 (15,16).…”
mentioning
confidence: 99%